Fire of life : the Smithsonian book of the Sun. - Smithsonian Institution (New York : distributed by Norton, 1981)
Twenty-eight essays discuss man's past and present knowledge of the sun, and its place in the arts, sciences, and humanities.
Includes index.
Booklist.
Library Journal.
Wilson's Senior High School.
Young Ad.-Adult.
Young Adult
Keywords: Photobiology; Solar energy; Solar energy; Sun; Sun